Representasi Feminisme Dalam Karya Sastra (Kajian Semiotika Sosial Novel “Eks Parasit Lajang” Karya Ayu Utami) - Radita Gora (Universitas Bina Sarana Informatika, 2015)
Literary texts into one media aspirational for individuals to build her mind in addressing the reality she sees. As with any novel titled Pengakuan Eks Parasit Lajang by Ayu Utami raised in regard feminism commodification of women in social, cultural and religious. Through social semiotic approach of Elaine Showalter who make criticisms of feminism in this work as a form of resistance against injustice and gender conflict. Keyword: feminism, semiotic approach